Peran Guru dalam Meningkatkan Kemampuan Literasi Peserta Didik di MIS Model Panyabungan (International Forum of Researchers and Lecturers, 2025)
The Role of Teachers in Improving Students' Literacy Skills in MIS Model Panyabungan''. This study aims to answer the focus of the research on: 1) how teachers improve students' literacy skills in MIS Model Panyabungan. 2) the role of teachers as educators in MIS Model Panyabungan. 3) Students' literacy skills in MIS Model Panyabungan. This study uses qualitative research. The research procedure used produces data in the form of written words, oral expressions from sources. Informants in this study involved the principal, head of the library, and teachers. Secondary data, obtained through literature studies, references, and documentation obtained from the results of the study. The results of the study showed that reading 15 minutes before starting learning for students, providing a reading corner, providing a library and adequate facilities and infrastructure for students, Teachers are also professional educators whose main task is to educate, teach and guide or evaluate students, teachers also have an important role in carrying out their duties here teachers become examples for students so that students want to exemplify how teachers behave so that good things emerge that students want to achieve.